2015
DOI: 10.1177/1941406414568562
|View full text |Cite
|
Sign up to set email alerts
|

An Explorative Qualitative Study of Experiences and Challenges to Exclusive Breastfeeding Among Mothers in Rural Zimbabwe

Abstract: Breastfeeding messages ought to be context specific, targeting custodians of tradition and belief systems, including men and significant others, to create a supportive and enabling environment for mothers to exclusively breastfeed."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(77 citation statements)
references
References 32 publications
12
52
0
1
Order By: Relevance
“…Mother's breastfeeding knowledge, such as knowing the advantages of breastfeeding and being aware of how to express and store breast milk, were also identified as facilitators of EBF. These findings are corroborated by various studies in other parts of the world [3,113,114]. Similarly, in the South East Asian region, a study conducted in Laos found that mothers older than 35 years tended to continue EBF for a year, although in contrast, those with low economic status were more likely to continue to breastfeed [115].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Mother's breastfeeding knowledge, such as knowing the advantages of breastfeeding and being aware of how to express and store breast milk, were also identified as facilitators of EBF. These findings are corroborated by various studies in other parts of the world [3,113,114]. Similarly, in the South East Asian region, a study conducted in Laos found that mothers older than 35 years tended to continue EBF for a year, although in contrast, those with low economic status were more likely to continue to breastfeed [115].…”
Section: Discussionsupporting
confidence: 74%
“…Support from family members (i.e. grandparents or the husband) was shown to have a positive impact on EBF, and this has been found in other studies [114,116,121,122,128,129]. Lack of family support was also identified as barrier in a study in India [130].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations